Determination of Thresholds of Radioactive Iodine Uptake Response With Clinical Exposure to Perchlorate: A Pooled Analysis. Issue 4 (April 2018) - Bruce, Gretchen M.; Corey, Lisa M.; Pearce, Elizabeth N.; Braverman, Lewis E.; Pleus, Richard C.
Abstract : Objective: To conduct a more robust examination of perchlorate exposure on iodide uptake inhibition (IUI) using pooled data from four clinical studies of perchlorate exposure. Methods: To establish a response threshold for IUI, data were analyzed using segmented linear regression and benchmark dose (BMD) analysis. Results: Segmented linear regression applied to data for 69 subjects representing nine doses identified a breakpoint corresponding to a change in the slope of the dose–response relationship of 3.0 mg/d perchlorate. The estimated BMD for a 20% decrease in iodine uptake was 2.3 mg/d, with a lower 95% confidence interval limit of 1.6 mg/d. Conclusions: A threshold dose for IUI from perchlorate exposure of 1.6 to 3.0 mg/d (0.021 to 0.038 mg/kg d) was estimated using two modeling approaches. These estimates are slightly higher than the lowest observed effect level of 0.02 mg/kg d from the Greer Study. Abstract : Supplemental Digital Content is available in the text